ENVIRONMENTAL CONDITION MEASUREMENT SYSTEM WITH A MINI WEATHER STATION USING ESP32 - Umar Muhammad; Irvawansyah; Dirham Muhammad (Jurusan Pendidikan Teknik Elektro, 2023)
Weather conditions are important to know because they have an impact on various human activities, such as agriculture, infrastructure, hydrology, and more. Several factors affect the weather, including wind speed, temperature, and air humidity. However, in this study, a mini weather station was designed to provide information not only on wind speed, temperature, and humidity but also on solar radiation. The research employed several sensors, including the DHT11, anemometer, and pyranometer. The research results indicate that the DHT11 error indoors is 1.4%, but it increases to 9% outdoors. The pyranometer shows a 3.62% error from direct solar radiation measurements. However, the wind speed sensor is still unstable, suggesting the need for improvement in future research.